Pengaruh Terapi Musik Klasik terhadap Tingkat Kecemasan Pada Ibu Hamil Primigravida Trimester III - Suharnah, Hijrianti; Jama, Fatma; S, Suhermi (Window of Nursing Journal, 2021)
Primigravida pregnancy is a condition that causes physical and psychological changes. One of the psychological aspects that affect pregnancy and can cause anxiety. This study aims to determine the effect of classical music therapy on anxiety levels in third trimester primigravida pregnant women at UPTD Puskesmas Turikale Kab. Maros. The research design used was a quasi experiment. The research design used was "One Group Pretest-Postest Design". The sample determination is done by total sampling technique with a sample size of 23 respondents. The intervention was given for 6 times of intervention for 2 weeks. The data analysis used was the Wilcoxon test data analysis with a significance level of Î± = 0.05. If the p value <0.05 then Ha is accepted, it means that there is an effect of the independent variable on the dependent variable The research results from statistical analysis using the Wilcoxon test obtained the value of Ï = 0.000, where the value of Ï is smaller than the value of Î± = 0.05, then Ha is accepted. The results of the study prove that there is an effect of classical music therapy on anxiety levels in Primigravida Trimester III pregnant women. The conclusion of this study is the effect of classical music therapy on the anxiety level of primigravida pregnant women. Before being given classical music therapy, the level of anxiety in the third trimester of primigravida pregnant women was mild anxiety, moderate anxiety and severe anxiety. Meanwhile, after being given classical music therapy intervention, there was a decrease in anxiety levels, namely not anxious, mild anxiety and moderate anxiety.